The Influence of Price, Location, and Service Quality on Customer Satisfaction at PUD Slaughterhouses in Medan City - Arif Andri Panjaitan; Hendra Saputra (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research aims to determine the influence of price, location and service quality on customer satisfaction at PUD slaughterhouses in Medan City. This research uses a quantitative method with a sampling technique using the Slovin formula. The population in this study were all customers who used services at the Medan City Animal Slaughter PUD from 1 August 2023 to 31 October 2023 which was obtained from customer data, namely 164 people. The data collection techniques used were observation and questionnaires. The data analysis technique used is a multiple linear regression model and hypothesis testing using the t test, F test and coefficient of determination. Previously the data had been tested using validity tests, reliability tests and classical assumption tests. Data processing uses the SPSS 29.0 for Windows program. Based on partial hypothesis testing, there is an influence of Price, Location and Service Quality on Customer Satisfaction at PUD Slaughterhouses in Medan City. Based on the research results, it shows that the variables Price, Location and Service Quality simultaneously influence Customer Satisfaction.